USEFULNESS OF FREE THYROXINE TO FREE TRIIODOTHYRONINE RATIO FOR DIAGNOSTICS OF VARIOUS TYPES OF HYPERTHYROIDISM - Jernej Grmek; Simona Gaberšček; Ajda Biček; Katja Zaletel (Zdravniški Vestnik, 2015)
Background: Different types of hyperthyroidism are treated differently. The correct diagnosis enables the adequate treatment. Clinical experiences suggest that free thyroxine (fT4) to free triiodothyronine (fT3) ratio is different for different types of hyperthyroidism. Considering the paucity of literature data on the topic our aim was to evaluate the role of the serum fT4 to fT3 (fT4/fT3)ratio in diagnostics of various types of hyperthyroidism. Methods: In retrospective clinical study we included 440 consecutive subjects, examined between February and August 2010, 350 females and 90 males aged between 15 and 97 years, among them 225 healthy subjects (HS), 80 patients with Graves' disease (GD), 48 with toxic adenoma (TA), 61 patients with hyperthyroid Hashimoto’s thyroiditis (HHT), 17 with subacute thyroiditis (ST), and 9 patients with iodine-induced hyperthyroidism (IIH). Thyrotropin (TSH), fT4, fT3 and thyroid autoantibodies were measured. The fT4/fT3 ratio was calculated. Results: The fT4/fT3 ratio was significantly different for various disorders causing hyperthyroidism (p<0.001). Compared with the fT4/fT3 ratio in HS (2.86±0.52), the ratio was significantly higher in HHT and ST (3.27±0.72 and 3.31±0.54, respectively, p<0.001 for both). In GD, the fT4/fT3 ratio was the lowest (2.55±0.58) and in IIH the highest (5.13±1.97). Both ratios significantly differed from the ratio in HS (p<0.001 for both) and in other hyperthyroid patients (p<0.001 for both). In patients with TA, the fT4/fT3 ratio was similar as in HS (2.85±0.71) (p=0.085). Conclusion: The fT4/fT3 ratio is different in various types of hyperthyroidism and therefore represents a useful tool in the diagnostic procedure.